Formulation and Evaluation of Hand Cream Using Cocoa Fat and Paste with the Addition of Ylang-Ylang (Cananga odorata) and Lilac (Syringa vulgaris) Essential Oils - Ikhwana, Yana; Aisyah, Yuliani; Irfan, Irfan; Yunita, Dewi (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2026)
Abstract: Cocoa fat and paste have the potential to be used in cosmetic products, especially because they can moisturize and hydrate the skin. The addition of essential oils to cosmetic products, besides providing a natural aroma, also functions as an antioxidant. This research aims to formulate and evaluate the characteristics of a hand cream based on cocoa fat and paste with the addition of ylang-ylang and lilac essential oils, which can remain free from fungal growth contamination after being stored for more than 30 days. The research was carried out in two stages: heating the cocoa fats and paste to temperatures of 25°C, 80°C, 90°C, and 121°C, and formulating the hand cream by varying the concentration of cocoa fat (1%, 2%, 3%) and the type of essential oil ((no essential oil, ylang-ylang oil, lilac oil, a blend of ylang-ylang and lilac oils). The total plate count analysis of the cocoa fats and paste showed that no microorganisms were found in the cocoa fat from a heating temperature of 25°C, while in the cocoa paste, microorganisms were not found after heating at a temperature of 121°C. The antioxidant activity of the cocoa fats and paste ranged after heating from 65.23% to 82.66%. The hand cream's characteristics met the quality standards of SNI 16-3499-1996 and BPOM No. 17 of 2014 including homogeneous appearance, pH, and specific gravity. Essential oils can be an alternative to using cocoa paste for scenting hand cream, because heating cocoa paste to 121°C for 15 minutes to eliminate microorganisms can reduce its antioxidant activity. Abstrak: Lemak dan pasta kakao memiliki potensi untuk digunakan dalam produk kosmetik terutama karena dapat melembapkan dan menghidrasi kulit. Penambahan minyak atsiri dalam produk kosmetik selain memberikan aroma alami juga berfungsi sebagai antioksidan. Penelitian ini bertujuan untuk memformulasi dan mengevaluasi karakteristik hand cream berbasis lemak dan pasta kakao dengan penambahan minyak atsiri ylang-ylang (Cananga odorata) dan lilac (Syringa vulgaris). yang dapat tetap bebas dari kontaminasi pertumbuhan jamur setelah disimpan lebih dari 30 hari. Penelitian dilaksanakan dalam 2 tahap, yaitu pemanasan lemak dan pasta kakao, menggunakan suhu 25°C, 80°C, 90°C, 121°C, dan formulasi hand cream dengan memvariasikan konsentrasi lemak kakao (1%, 2%, 3%), dan jenis minyak atsiri (tanpa minyak atsiri, minyak ylang-ylang, minyak lilac, campuran minyak ylang-ylang dan lilac). Hasil analisis total plate count (TPC) lemak dan pasta kakao menunjukkan bahwa pada lemak kakao sudah tidak ditemukan adanya mikroorganisme mulai suhu pemanasan 25°C, sedangkan pada pasta kakao, tidak ditemukan mikroorganisme setelah proses pemanasan pada suhu 121°C. Aktivitas antioksidan lemak dan pasta kakao setelah pemanasan berkisar 65,23% - 82,66%. Hand cream telah memiliki karakteritik sesuai syarat mutu SNI 16-3499-1996 dan BPOM No. 17 tahun 2014 yaitu penampakan homogen, pH (4,60–6,58), dan bobot jenis (0,95–1,05). Minyak atsiri dapat menjadi alternatif untuk menggantikan penggunaan pasta kakao sebagai sumber aroma pada hand cream, mengingat pemanasan pasta kakao pada suhu 121°C selama 15 menit dapat menurunkan aktivitas antioksidan dari pasta kakao.